Semantic enrichment of material in the field of Linked Open Data - Agenjo-Bullón, Xavier; Hernández-Carrascal, Francisca (Anuario ThinkEPI, 2022)
The main objective of reconciliation and semantic enrichment strategies for subject matter is described: in line with the philosophy of the semantic web, offering the user different ways to search for similar subjects in other information systems located in different parts of the web. These reconciliation and enrichment techniques must form a hybrid procedure of manual, semiautomatic, and automatic operations involving different programs and applications that enable the processing of large datasets at an affordable final cost for cultural institutions. Its application must follow good practices, guidelines, and recommendations, including the W3C, Europeana, and the FAIR principles. Some of the key vocabulary from Spanish material available on Linked Open Data are analyzed for their multilingual capacities. The importance of having standardized reconciliation services available to select Linked Open Data sources for reconciliation and semantic enrichment is noted. It is concluded that the information systems of cultural institutions must offer functionalities that involve the use of enriched subject authority records for searching, navigating, visualizing, and exporting.
Keywords: Semantic enrichment; Data reconciliation; Subject authority records; Linked Open Data